INFLUENCE OF THE APPLIED PRESSURE ON FINGER JOINED END-TO-END WOOD - Petkov, Todor; Mihailov, Vladimir (Innovation in Woodworking Industry and Engineering design, 2020)
In the production of finger-jointed details, it is most important to provide the required applied pressure to achieve the desired adhesion strength of the joint. The results of the study of beech wood elements (Fagus Sylvatica) are presented, with applied different pressure for the face ends of the details (0,4 and 0,7 N/mm2). The following properties have been determined of the tested samples: bending strength, modulus of elasticity and the density of wood. The pneumatic-piston system also provided for securing the bonding pressure in the longitudinal direction of the wood. In the carried – out experiments, it was used a polyvinyl acetate adhesive with a class of water resistance D3. The mechanical properties of the glued elements depend on their structure, the type of adhesive and the type of wood. The paper presents the values of strength and modulus of elasticity in static bending of elements derived from beech wood.